Comparative Analyses of with Functional Predictions - Xiang-Ping Wang (Bioinformatics and Biology Insights, 2010)
Background Cytoplasmic polyadenylation element binding proteins (Cpebs) are a family of proteins that bind to defined groups of mRNAs and regulate their translation. While Cpebs were originally identified as important features of oocyte maturation, recent interest is due to their prospective roles in neural system plasticity. Results In this study we made use of bioinformatic tools and methods including NCBI Blast, UCSC Blat, and Invitrogen Vector NTI to comprehensively analyze all known isoforms of four mouse Cpeb paralogs extracted from the national UniGene, UniProt, and NCBI protein databases. We identified multiple alternative splicing variants for each Cpeb. Regions of commonality and distinctiveness were evident when comparing Cpeb2, 3 , and 4. In addition, we performed cross-ortholog comparisons among multiple species. The exon patterns were generally conserved across vertebrates. Mouse and human isoforms were compared in greater detail as they are the most represented in the current databases. The homologous and distinct regions are strictly conserved in mouse Cpeb and human CPEB proteins. Novel variants were proposed based on cross-ortholog comparisons and validated using biological methods. The functions of the alternatively spliced regions were predicted using the Eukaryotic Linear Motif resource. Conclusions Together, the large number of transcripts and proteins indicate the presence of a hitherto unappreciated complexity in the regulation and functions of Cpebs. The evolutionary retention of variable regions as described here is most likely an indication of their functional significance.